On the Isomorphism in the parables of Jesus - HU, Rong (Journal of Research for Christianity in China (JRCC), 2022)
Based on the author’s definition of the structure of Jesus’s parables in other article, this article analyzed the isomorphism of the language relationship between the parables’s text and their relevant explanation in the synoptics. it’s the conclusion that the isomorphism is one of the essential elements of the parables of Jesus. Above all, since Jesus set the parables with the isomorphic thinking model, following the way of Jesus to interpret the parables is the straight way to it.